La práctica dicente-investigativa desdela tecnología educativa y el socio- constructivismo - Robles-Altamirano, Adriana; Barreno-Salinas, Zoila (Ciencia UNEMI, 2016)
A time of changes is experienced related to the current techno-scientific paradigm and education is no an exception. From the socio-constructivist theory of learning and the use of the information and communication technology (ICT) in education, a more meaningful and autonomous learning is justified which is based on researching of learners. The socio-constructivism proposes the participation of students within a group learning project, which will enhance their ability to solve contextualized problems, allowing them to develop a social construction process of knowledge, supported by technological tools at their fingertips. This work aims to demonstrate that autonomous learning with the use of research is possible if a socio-constructivist approach to learning with the support of educational technology is applied.